Development Of Non-Ionic Silicone Surfactant-Based Extraction Methods Of Triazine Herbicides In Milk And Water Samples - Mohd, Nur Izzaty (2018)
Cloud point extraction (CPE) – spectrophotometric method had been developed for separation of atrazine and propazine using non-ionic silicone surfactant, polysiloxane polyether, as a new approach of triazine compounds extractor in the CPE. This type of surfactants was chosen as a green extraction solvent because of its structure and properties. There were two types of polysiloxane polyether (OFX 0309 and DC 193C) were studied in the CPE to investigate their effectiveness as extractor toward triazine compounds. Performance recovery of CPE can be observed when the following conditions was applied; CPE-OFX 0309, 1.0 mL 0.4 v/v % surfactant concentration, solution pH at 5, 2.0 M of Na2SO4, incubation time for 15 minute at 50 °C dan sample volume of 1mL at concentration of 10 mg/L while for CPE-DC 193C; the same conditions was applied except for concentration of salt used (1.5 M of Na2SO4). Using the optimized parameters, CPE was applied in milk and water samples. Langmuir model was found to fit well with the solubilization of the triazine compounds into the OFX 0309 and DC193C surfactant. Thus, Langmuir isotherm has been used to explain the solubilization study between surfactant and triazine compounds. The thermodynamic parameters were determined such as Gibbs free energy (ΔGº) which increases with temperature, value of enthalpy (ΔHº) and value of entropy (ΔSº) which increase with the surfactant hydrophobicity. The thermodynamic results indicated that the solubilization of the triazine compounds solubilized into the both surfactants were feasible, spontaneous and endothermic.